2007
DOI: 10.1179/135100007x162211
|View full text |Cite
|
Sign up to set email alerts
|

Role of 4-hydroxynonenal and its metabolites in signaling

Abstract: Available evidence from a multitude of studies on the effects of 4-hydroxynonenal (HNE) on cellular processes seem to converge on some common themes: (i) concentration-dependent opposing effects of HNE on key signaling components (e.g. protein kinase C, adenylate cyclase) predict that certain constitutive levels of HNE may be needed for normal cell functions - lowering of this constitutive HNE level in cells promotes proliferative machinery while an increase in this level promotes apoptotic signaling; (ii) HNE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 45 publications
3
105
0
Order By: Relevance
“…This is a product of lipid oxidation that has been shown to modulates ligand-independent signaling by membrane receptors and interacts with a variety of kinases [53]. Recently it was found that mice mutant for the glutathione transferase mGSTA4-4, an enzyme implicated in the detoxification of 4-hydroxynonenal (4-HNE) have an extended lifespan despite higher levels of this product of lipid oxidation [54].…”
Section: Ros Signaling Affects Aging and Lifespanmentioning
confidence: 99%
“…This is a product of lipid oxidation that has been shown to modulates ligand-independent signaling by membrane receptors and interacts with a variety of kinases [53]. Recently it was found that mice mutant for the glutathione transferase mGSTA4-4, an enzyme implicated in the detoxification of 4-hydroxynonenal (4-HNE) have an extended lifespan despite higher levels of this product of lipid oxidation [54].…”
Section: Ros Signaling Affects Aging and Lifespanmentioning
confidence: 99%
“…The chemical basis of action of the aldehydes that results in apoptosis is unknown, but recent research indicates that HNE is a signaling molecule at subtoxic concentrations (70,(72)(73)(74), modulating MAP kinases, PKC isoforms, cell cycle regulators, receptor tyrosine kinases, and caspases and activating the JNK-c-Jun/ AP-1 pathway (75). Subtoxic concentrations of HNE were also observed to induce expression of various antioxidant/detoxification enzymes (76).…”
Section: Oxidative Stress and Neurodegenerative Disease--general Consmentioning
confidence: 99%
“…A number of recent reviews covering studies on the role of HNE in the modulation of signaling processes are also available [2][3][4][17][18][19][20][21][22][23][24]. Most of these reviews have focused on the role of HNE in inducing apoptosis, regulation of the expression of genes, and its interactions with target proteins including the components of various signaling cascades.…”
Section: Introductionmentioning
confidence: 99%